1 REIMAGINING CONTENT: DYNAMIC AND CREATIVE IMAGERY FOR SPECIAL EDUCATION USING AR TECHNOLOGY - Ramachadran, Divya (Digital Repository of Theses, 2023)
Technology is the new teaching aid. The use of AR technology to enhance learning and engagement has increased tremendously over the years. However, in special education, technology and the use of digital devices are heavily encouraged in the classrooms to provide a deeper, more effective, and more wholesome experience for kids. Personalization for promoting inclusive learning using AR is also a growing area of interest in the learning skills domain. Individuals with special needs are identified to experience deficits in learning categorical vocabularies and using languages in different contexts. This includes learning many subjects, in particular Science and Math. Vocabulary acquisition is very important for independent living and literacy skills and science are considered valuable for individuals with special needs. Hence the requirement for better and more efficient AR imagery to enhance the learning of vocabulary for special students. This proposal looks into the creative quality of the images needed in language, particularly in learning new words for the special child. It delves deep into how language is interpreted by special children on how to bring effective dynamic imagery using AR into the space to make learning effective, simple, and engaging. Quality and type of imagery needed for such children, which would induce better learning would be looked into, allowing us to create a metric system for the kind of images created for more engaging learning. This could be a set of guidelines for AR image creators for special education purposes. This would not only help educators in classrooms but also help learning and development centers devise more apt learning programs for disabled students using AR tech.